Culturally proficient practice : supporting educators of English learning students - Quezada, Reyes L.; Lindsey, Delores B.; Lindsey, Randall B. (Corwin Press, 2012)
Help your English learning students achieve academic success!Designed to empower educators to become agents of change in their classrooms, schools, and communities, this guide introduces the principles of Cultural Proficiency and how they can help improve educators' ability to effectively teach English language learners. This book features: Activities that build core Cultural Proficiency skills and promote personal transformation A chapter-by-chapter rubric for working effectively with English learning students A conversation-starting case story featuring the River View School Distr.